Probing the shot behaviour in Cygnus X-1 using simultaneous AstroSat-NICER observation. Issue 4 (28th March 2022) - Bhargava, Yash; Hazra, Nandini; Rao, A R; Misra, Ranjeev; Bhattacharya, Dipankar; Roy, Jayashree; Alam, Md Shah
ABSTRACT: We analyse the aperiodic flaring features, also known as shots, observed in Cyg X-1 in the 0.1–80 keV energy band using a 6.39 ks simultaneous observation with AstroSat and Neutron star Interior Composition ExploreR ( NICER ). We detect 49 simultaneous shots in the soft and hard X-ray bands with NICER and AstroSat -LAXPC, respectively. We observe the shot profile for the first time in soft X-rays (0.1–3 keV), which shows a spectral peak at ∼2 keV. Using time-averaged spectroscopy, we measured the truncation of the inner accretion disc at 6.7 ± 0.2 gravitational radii. The shot-phase-resolved spectroscopy allowed us to identify the origin of some of the brightest aperiodic peaks in the soft X-rays. We find that the accretion rate is consistent with a constant during the shots while the inner edge of the accretion disc moves inwards/outwards as these shots rise/decay. We discuss the possible mechanisms causing the swing in the inner radius.